2006
DOI: 10.1063/1.2220051
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a pitchfork bifurcation in thermal convection flow inside an isosceles triangular cavity

Abstract: Transient, laminar thermal convection of air confined to an isosceles triangular cavity heated from the base and symmetrically cooled from the upper inclined walls has been investigated numerically. The system of conservation equations, subject to the proper boundary conditions, along with the equation of state assuming the air behaves as a perfect gas are solved with the finite volume method. In the conservation equations, the second-order-accurate QUICK scheme was used for the discretization of the convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…The main objective of their research was to validate the existence of the numerical prediction of the symmetry-breaking bifurcation of the heated air currents that arise with gradual increments in Rayleigh number. Ridoune and Campo [15] and Lei et al [16] have also investigated the numerical prediction of the symmetry-breaking bifurcation. However, water has been used as the working fluid by Lei et al [16].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main objective of their research was to validate the existence of the numerical prediction of the symmetry-breaking bifurcation of the heated air currents that arise with gradual increments in Rayleigh number. Ridoune and Campo [15] and Lei et al [16] have also investigated the numerical prediction of the symmetry-breaking bifurcation. However, water has been used as the working fluid by Lei et al [16].…”
Section: Introductionmentioning
confidence: 98%
“…However, water has been used as the working fluid by Lei et al [16]. Ridoune and Campo [15] reported that as Ra is gradually increased, the symmetric plume breaks down and fades away. Thereafter, a subcritical pitchfork bifurcation is created giving rise to an asymmetric plume occurring at a critical Rayleigh number, Ra ¼ 1.42 Â 10 5 .…”
Section: Introductionmentioning
confidence: 98%
“…The observed asymmetric flow structure in the isosceles triangular enclosure was previously reported by Holtzmann et al [7] in the case with constant cooling at the inclined surfaces and simultaneous heating at the base. The formation of the asymmetric flow is due to a pitchfork bifurcation as discussed by Ridouanea and Campo [6] At t = 2.8125 P , Figure 2 In Figure 2(f) the large cell has crossed the centreline of the cavity and the smaller cell, closer to this large cell, fills up this gap and grows itself. The flow is then gradually returning to symmetry.…”
Section: C685mentioning
confidence: 98%
“…However, many of the recent works are targeted more towards the application aspect of the process. Ridouane et al [32] and Ridouane and Campo [33] studied extensively the natural convection in an isosceles triangle and right triangular cavity in their work. Ben-Nakhi and Mahmoud [34] studied the natural convection in roof cavities inside buildings.…”
Section: Introductionmentioning
confidence: 99%